OPTIMIZED RELAY LENS DESIGN FOR HIGH-RESOLUTION IMAGE TRANSMISSION IN MILITARY TARGET DETECTION SYSTEMS - Çelik, Burak; Kıvanç,; Taşkın, Ezgi; Akbal, Ayhan; Orhan, Ahmet (My University, 2025)
The design and performance analysis of relay lenses that provide high-performance image transmission for target acquisition and tracking in military optical systems. Relay lenses are critical components for clear and lossless image transmission over long distances. In this study, the optical performance of a relay lens system designed and optimized using ZEMAX software is investigated in detail. The analysis focuses on important optical properties such as modulation transfer function (MTF), spot diagrams, Seidel diagram, field curvature and distortion. The results show that the lens has significant potential in military applications for target detection and tracking with high resolution and low aberration.
Keywords: Military Optical Systems; Zemax; Relay Lens; Lens Design